Cocatalyst engineering of a narrow bandgap Ga-La5Ti2Cu0.9Ag0.1O7S5 photocatalyst towards effectively enhanced water splitting. Issue 48 (30th November 2021) - Xiao, Qi; Xiao, Jiadong; Vequizo, Junie Jhon M.; Hisatomi, Takashi; Nakabayashi, Mamiko; Chen, Shanshan; Pan, Zhenhua; Lin, Lihua; Shibata, Naoya; Yamakata, Akira; Takata, Tsuyoshi; Domen, Kazunari
Abstract : The hydrogen evolution activity of Ga-doped La5 Ti2 Cu0.9 Ag0.1 O7 S5 (Ga-LTCA) was boosted by loading a Rh cocatalyst having uniform dispersion and intimate contact. Abstract : Ga-La5 Ti2 Cu0.9 Ag0.1 O7 S5 (Ga-LTCA), an oxysulfide photocatalyst, can act as a hydrogen evolution photocatalyst in Z-scheme water splitting systems in conjunction with an oxygen evolution photocatalyst (OEP) under visible light irradiation up to 700 nm. However, the overall efficiency is strongly limited by the low activity of Ga-LTCA. The present work demonstrates a drastic improvement in the H2 evolution activity of Ga-LTCA after loading small Rh cocatalyst particles exhibiting uniform dispersion and intimate contact with the photocatalyst. Using this system, an apparent quantum yield (AQY) of 11.2 ± 0.9% at 420 nm was obtained for H2 evolution from an aqueous Na2 S–Na2 SO3 solution, this being the highest value yet reported for a sacrificial H2 evolution reaction using an oxysulfide photocatalyst. Following modification with a Cr2 O3 layer, efficient Z-scheme water splitting was also accomplished using the cocatalyst-loaded Ga-LTCA in combination with H + /Cs + /PtO x /WO3 as the OEP, with an improved AQY of 2.4% at 420 nm.